Spotlight on the Energy Harvest of Electroactive Microorganisms: The Impact of the Applied Anode Potential - Korth, Benjamin; Harnisch, Falk (Frontiers in Microbiology, 2019)
Electroactive microorganisms (EAM) harvest energy by reducing insoluble terminal electron acceptors (TEA) including electrodes via extracellular electron transfer (EET). Therefore, compared to microorganisms respiring soluble TEA, an adapted approach is required for thermodynamic analyses. Based on bioenergetic fundamentals, only a fraction of the energy difference between electron donor and TEA is exploited via the electron-transport chain to generate proton-motive force being subsequently utilized for ATP synthesis. However, according to a common misconception, the anode potential is supposed to immediately influence the energy harvest of EAM. By comparing the model organism Geobacter spp. and microorganisms respiring soluble TEA, we reason that a considerable part of the electron-transport chain of EAM performing direct EET does not contribute to the build-up of proton-motive force and thus microbial energy harvest. Furthermore, by using a modeling platform, it is demonstrated that the influence of anode potential on energy harvest is solely a kinetic effect. When facing a low anode potential, NADH is accumulating due to a low driving force for direct EET representing thermodynamically unfavorable reaction conditions for acetate oxidation. With anode potentials ≥ 0.2 V (vs. SHE), reaction conditions for acetate oxidation are improved and a further potential increase does not result in higher energy harvest. Therefore, the thermodynamic window of opportunity is fully exploited by Geobacter spp. if the anode potential is set to 0.2 V. Considering the restricted energy harvest of EAM is a prerequisite to improving thermodynamic analyses, microbial resource mining, and to transfer microbial electrochemical technologies into practice.